Study of antibiotics resistance for Enterococcus faecalis isolated from different clinical casea in Al- Diwaniyah city - Al-musawi, A. N.H.; Al-garawi, H.S.M. (Al-Qadisiyah Journal of Pure Science, 2017)
Twenty tow hundred samples were collected from different clinical cases of Diwaniyah Educational Hospital and Maternity and Children Hospital in the city of Diwaniya , for the period from 20/11/2012 until 12/04/2013 . This study showed there were 20 isolates of Enterococcus faecalis .This isolates distribted :10 isolates from infections urinary tracts and 10 isolates from cases of diarrhea while not isolated from infections of wounds and burns. Adopted qualities cultures and microscopic bacteria studied, and tests biochemical , as diagnostic center Chrom agar and then the final diagnosis by a Vitek 2. conducted screening sensitivity to isolates studied direction (11), Susciptibity test was shown that isolates were resistant absolute direction antibiotics Erythromycin and Tetracycline and Rifampin and Ciprofloxacin and 100% , while showed these bacteria sensitivity of the absolute direction of anti Imipenem and by 100 % , and varied the direction of anti - resistance Chloramphenicol , Nitrofurantoin and Penicillin Gentamycin and Vancomycin , with 50 % , 85% , 60 % , 70 % and 35 %, respectively. As the proportion of the total resistant to E.faecalis isolates the total antibiotic used in the study are higher than the sensitivity in terms of resistance to more than 70% of these antibiotics.